Diagnosis of Idiopathic GHD in Children Based on Response to rhGH Treatment: The Importance of GH Provocative Tests and IGF-1 - Felício, João Soares; Janaú, Luísa Corrêa; Moraes, Marcelle Alves; Zahalan, Nathalie Abdallah; de Souza Resende, Fabrício; de Lemos, Manuela Nascimento; de Souza Neto, Norberto Jorge Kzan; Farias de Franco, Isabela Imbelloni; Leitão, Loyane Tamyres Costa; Silva, Lilian de Souza d'Albuquerque; de Oliveira, Maria Clara Neres Iunes; de Alcântara, Angélica Leite; et al. (Frontiers in Endocrinology, 2019)
Purpose:Serum IGF-1(Insulin like growth factor 1) and Growth Hormone (GH) provocative tests are reasonable tools for screening and diagnosis of idiopathic GH Deficiency (IGHD). However, the average cut-off points applied on these tests have a lower level of evidence and produce large amounts of false results. The aim of this study is to evaluate the sensitivity, specificity and accuracy of IGF-1 and GH stimulation tests as diagnostic tools for IGHD, using clinical response to recombinant human GH (rhGH) treatment as diagnostic standard (increase of at least 0.3 in height standard deviation (H-SD) in one year). Methods: We performed a prospective study with 115 children and adolescents presenting short stature (SS), without secondary SS etiologies such as organic lesions, genetic syndromes, thyroid disorders. They were separated into Group 1 (patients with familial SS or constitutional delay of growth and puberty, not treated with rhGH), Group 2 (patients with suspicion of IGHD with clinical response to rhGH treatment) and Group 3 (patients with suspicion of IGHD without growth response to rhGH treatment). Then, they were assessed for diagnostic performance of IGF-1, Insulin Tolerance Test(ITT) and clonidine test(CT) alone and combined at different cut-off points. Results:Based on the ROC curve, the best cut-off points found for IGF-1, ITT and CT when they were used isolated were -0.492 SDS (sensitivity: 50%; specificity: 53.8%; accuracy: 46.5%), 4.515 µg/L (sensitivity: 75.5%; specificity: 45.5%; accuracy: 52.7%) and 4.095 µg/L (sensitivity: 54.5%; specificity: 52.6%; accuracy: 56.9%), respectively. When we had combined IGF-1 with -2SD as cut-off alongside ITT or CT, we found 7µg/L as the best cut-off point. In this situation, ITT had sensitivity, specificity and accuracy of 93.9%, 81.8% and 90.1%, while CT had 93.2%, 68.4%, and 85.7%, respectively. Conclusion:Our data suggest that diagnosis of IGHD should be established based on a combination of clinical expertise, auxologic, radiologic and laboratorial data, using IGF-1 at the -2SD threshold combined, with ITT or CT at the cut-off point of 7µg/L. Additional studies, similar to ours, are imperative to establish cut-off points based on therapeutic response to rhGH in IGHD, which would be directly related to a better treatment outcome.